(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
As a result of our research in Armenia were established 59 species of poisonous macromycetes, which belong to 16 genera, 10 families and 5 orders. The largest numbers of poisonous species are found in North-Eastern regions of the Republic. According to the data of the Ministry of Healthcare of RA, in 2014–2016 on the entire territory of the Republic were registered 147 poisoning cases with fungi.